Determinan Status Gizi Balita pada Keluarga Petani di Wilayah Kerja Puskesmas Halilulik Kabupaten Belu Tahun 2019 - Evalina Joana Doutel; Intje Picauly; Johny A. R. Salmun (Universitas Nusa Cendana, 2019)
Toddlers are vulnerable groups that must be considered especially the fulfillment of nutritional intake. Balanced nutrition in infancy plays an important role in increasing human resources in the future, but malnutrition in infancy affects the growth and development of children's brains that are irreversible or unable to recover. The problem of malnutrition is still a major problem in Indonesia despite the many efforts and prevention programs that have been made. This study aims to analyze the determinant of toddler nutrition status in farmer's families in Halilulik Health Center Belu District in 2019. This research used an analytic survey with a cross-sectional design. The sample in this research were 94 toddlers who were in the Halilulik Health Center Community. Data analysis used was univariate analysis, bivariate analysis and multivariate analysis with chi-square and multiple logistic regression tests. The results of this research showed that the variables of mother's knowledge (ρ=0.032), level adequacy of energy (ρ = 0,000), level adequacy of protein (ρ=0,000) and history of infectious disease (ρ=0,002) have correlation with Toddler Nutrition Status, while families food processing habits (ρ=0,739) and families eating restrictions (ρ=0,617) did not have any correlation with Toddler Nutrition Status. The dominant factor that most influences the nutritional status of toddlers is the level adequacy of energy followed by the level adequacy of protein. Nutrition toddlers have less levels of energy and protein intake compared to toddlers with good nutritional status. Consumption of foods that are diverse and varied needs to be considered, especially foods that are sourced with energy, protein, and fat to reduce the problem of malnutrition in infants.